A critique of Tadeusz Swietochowski’s works on the Azerbaijan Democratic Republic (1918-1920) under the prism of Edward Said’s Orientalism - Huseynov, Elchin Shahinovich; Tunku Mohd Mokhtar, Tunku Mohar (IIUM Press, International Islamic University Malaysia, 2019)
The Azerbaijan Democratic Republic (1918-1920) (which shall, henceforth, be referred to as ADR) was an independent state which existed for 23 months and laid the ground for the future of Azerbaijan. Today’s Azerbaijan is the inheritor and successor of the ideals and values of the ADR. In 2018, Azerbaijanis around the world celebrated the 100th anniversary of the ADR that showed the importance of this political event in the socio-political life of the nation. This article investigates the “Orientalist” points of view on the ADR in the works of “Azerbaijanist”, Tadeusz Swietochowski. It analyses the standpoints that relegate the importance of this political event. The article provides a contextual analysis in order to find those points. The research found that not all the points on the ADR in Swietochowski’s works are reliable. Some of Swietochowski’s works were written decades ago before the USSR’s dissolution, when the archives were under Soviet confidentiality. Despite the monopoly of Swietochowski in this field, the research suggests taking into consideration the newly discovered documents while studying the political events of the end of the 19th and the beginning of the 20th centuries for the objective outcomes.